Parasites of freshwater fishes in North America: why so neglected? - Scholz, Tomáš; Choudhury, Anindo (The Journal of parasitology, 2014)
Fish parasitology has a long tradition in North America and numerous parasitologists have contributed considerably to the current knowledge of the diversity and biology of protistan and metazoan parasites of freshwater fishes. The Journal of Parasitology has been essential in disseminating this knowledge and remains a significant contributor to our understanding of fish parasites in North America as well as more broadly at the international level. However, with a few exceptions, the importance of fish parasites has decreased during the last decades, which is reflected in the considerable decline of funding and corresponding decrease of attention paid to these parasites in Canada and the United States of America. After the 'golden age' in the second half of the 20th Century, fish parasitology in Canada and the United States went in a new direction, driven by technology and a shift in priorities. In contrast, fish parasitology in Mexico has undergone rapid development since the early 1990s, partly due to extensive international collaboration and governmental funding. A critical review of the current data on the parasites of freshwater fishes in North America has revealed considerable gaps in the knowledge of their species composition, host specificity, life cycles, evolution, phylogeography, and relationships with their fish hosts. As to the key question, "Why so neglected?" this is probably because: (1) fish parasites are not in the forefront due to their lesser economic importance; (2) there is little funding for this kind of research, especially if a practical application is not immediately apparent; and (3) of shifting interests and a shortage of key personalities to train a new generation (they switched to marine habitats or other fields). Some of the opportunities for future research are outlined, such as climate change and cryptic species diversity. A significant problem challenging future research seems to be the loss of trained and experienced fish parasitologists. This has 2 major ramifications: the loss of expertise in identifying organisms that other biologists (e.g., ecologists, molecular biologists, evolutionists) work with, and an incomplete comprehension of ecosystem structure and function in the face of climate change, emerging diseases, and loss of biodiversity.
Keywords: Myxozoa; periodika jako téma; Leeches; nemoci ryb; North America; Severní Amerika; ryby; Fish Diseases; History, 21st Century; Parasitic Diseases, Animal; Periodicals as Topic; dějiny 20. století; History, 20th Century; dějiny 21. století; parazitární nemoci u zvířat; zvířata; Crustacea; parazitologie; Ciliophora; sladká voda; cizopasní červi; Fishes; Helminths; pijavice; Fresh Water; opomíjené nemoci; Neglected Diseases; korýši; Animals; Kinetoplastida; Parasitology; Microsporida